The Influence of Price, Service Quality on Customer Satisfaction and Loyalty at Grojogan Sewu Nature Park - Yusuf Ahmad Abdullah; Ihwan Susila (Jurnal Indonesia Sosial Sains, 2024)
Tourism is an important sector in national development. Competition for tourist destinations, including Grojogan Sewu Nature Tourism Park, is getting tighter. To compete, managers must offer competitive prices and quality services. Precise price and good service are not only attractive, but also retain customers. Customer satisfaction is the key to success, as it has an impact on loyalty and positive recommendations. The purpose of this study is to see how price and service quality affect customer happiness and loyalty at Grojogan Sewu Nature Tourism Park in Karanganyar. The research method adopted was quantitative. Data was collected via a questionnaire completed by 100 visitors to the location. The analysis technique employed was Partial Least Squares-Structural Equation Modeling (PLS-SEM) utilizing SMARTPLS 3.0 software. The study's findings reveal that pricing and service quality have a positive and significant influence on customer satisfaction, which in turn has a favorable and significant effect on customer retention. This demonstrates how right pricing and outstanding service may boost customer happiness and loyalty at Grojogan Sewu Nature Tourism Park.